Modified magnetic mercury-removal adsorbent, preparation method and application thereof
Patent Information
- Application Number
- CN202611467513.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
(1)不同氯化物体系稳定性差异带来的应用局限:目前较为常见的是采用CuCl2通过常规浸渍-热干燥方法对磁珠进行改性,该体系在一定程度上可实现Hg0的有效去除
(1)本发明有效抑制FeCl3水解,实现Cl元素高保留,相比传统浸渍-热干燥法(Cl元素基本水解和挥发),低温冷冻干燥法制备的吸附剂表面Cl元素质量分数基本维持不变,为后续脱汞反应提供了充足的氧化位点。
Smart Images

Figure CN122974291A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of air pollution control and functional material preparation technology, and in particular to a modified magnetic mercury removal adsorbent, its preparation method and application. Background Technology
[0002] Mercury (Hg), as a persistent and toxic pollutant worldwide, has garnered widespread international attention for its environmental and health risks. Among the various forms of mercury produced during coal combustion, elemental mercury (Hg) is the most prevalent. 0 Mercury, due to its high volatility, chemical inertness, and poor water solubility, is difficult to remove using conventional pollution control technologies, making it a key challenge in flue gas purification. Currently, the most widely used industrial technology, activated carbon injection (ACI), has significant limitations: on the one hand, to meet increasingly stringent emission standards, large amounts of activated carbon are required, leading to a significant increase in operating costs (approximately US$60,000 to US$100,000 per kg of mercury removed); on the other hand, activated carbon after mercury adsorption enters the fly ash system, reducing the quality of fly ash and affecting its resource utilization. Against this backdrop, developing recyclable magnetic mercury removal adsorbents has become an important research direction. Utilizing naturally occurring magnetic beads (MF) in coal fly ash as a carrier has advantages such as wide availability and low cost. Existing technologies modify magnetic beads by introducing active components such as Cu and Cl, which can, to some extent, increase the mercury adsorption capacity. 0 The removal capacity is good. However, this type of Cu / Cl-modified technology still has certain limitations. To reduce costs and corrosion risks, researchers have proposed using iron-based chlorides (such as FeCl3) to replace CuCl2 in the mercury removal system. However, FeCl3 is sensitive to liquid water environment and temperature conditions during conventional impregnation-heat drying processes, and is prone to hydrolysis, causing the Cl active component to volatilize and be lost in the form of HCl, making it difficult to achieve stable loading, which has become a key problem restricting the application of iron-based systems. Specifically: (1) Application limitations caused by the difference in stability of different chloride systems: At present, the most common method is to use CuCl2 to modify magnetic beads by conventional impregnation-heat drying method. This system can achieve Hg to a certain extent 0 Effective removal of [the substance]. However, when FeCl3 is used as the active component, its stronger hydrolysis tendency makes it difficult to achieve stable loading under traditional process conditions, limiting the application potential of the iron-based low-cost system; (2) Conventional impregnation-thermal drying process leads to severe loss of Cl: During FeCl3 loading, conventional thermal drying (usually above 100℃) accelerates its hydrolysis reaction in a liquid water environment, causing Cl to volatilize and escape in the form of HCl, resulting in a significant reduction in the effective Cl content on the surface. This process not only reduces the density of active sites but also changes the form of active components, thereby weakening the resistance to Hg. 0 Oxidizing ability; (3) Uneven distribution of active sites and densification of structure: During the heat drying process, the active components in the solution migrate with the water and undergo local enrichment or aggregation, which easily forms an uneven and even dense coating layer on the surface of the carrier, limiting Hg 0 Diffusion into internal active sites further affects mercury removal efficiency. Summary of the Invention
[0003] In view of this, the purpose of this invention is to provide a modified magnetic mercury removal adsorbent, its preparation method, and its application. The modified magnetic mercury removal adsorbent prepared by this invention can achieve stable loading and efficient utilization of Cl element, significantly improving the removal of Hg. 0 Adsorption performance.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a modified magnetic mercury removal adsorbent, comprising the following steps: Modified magnetic beads were obtained by impregnating magnetic beads with FeCl3 solution; The modified magnetic beads are subjected to freeze treatment to obtain the modified magnetic mercury removal adsorbent. The freeze treatment includes sequential quick freezing and freeze drying, and the quick freezing temperature is -10°C. The concentration of the FeCl3 solution is 3~9wt%.
[0005] Preferably, the quick-freezing time is 2 to 6 hours.
[0006] Preferably, the impregnation is an in-situ impregnation with equal volume.
[0007] Preferably, the ratio of FeCl3 solution to magnetic beads is 0.15~0.18 mL: 1 g.
[0008] Preferably, the impregnation process further includes sequential ultrasonic treatment and static setting.
[0009] Preferably, the temperature of the ultrasonic treatment is 5~10℃.
[0010] Preferably, the freeze-drying temperature is 0~10℃, the pressure is 10Pa, and the time is 24~48h.
[0011] The present invention also provides a modified magnetic mercury removal adsorbent prepared by the preparation method described above, wherein the mass fraction of Cl element in the modified magnetic mercury removal adsorbent is 0.307~1.23%.
[0012] This invention also provides the application of the modified magnetic mercury removal adsorbent described in the above technical solution in the field of mercury removal from flue gas.
[0013] This invention provides a method for preparing a modified magnetic mercury removal adsorbent, comprising the following steps: impregnating magnetic beads with FeCl3 solution to obtain modified magnetic beads; subjecting the modified magnetic beads to freeze treatment to obtain the modified magnetic mercury removal adsorbent, wherein the freeze treatment includes sequential quick-freezing and freeze-drying, the quick-freezing temperature being -10℃; and the concentration of the FeCl3 solution being 3~9wt%.
[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention effectively inhibits the hydrolysis of FeCl3 and achieves high retention of Cl element. Compared with the traditional impregnation-heat drying method (Cl element is basically hydrolyzed and volatilized), the mass fraction of Cl element on the surface of the adsorbent prepared by the low temperature freeze drying method remains basically unchanged, providing sufficient oxidation sites for subsequent mercury removal reaction.
[0015] (2) The present invention constructs a uniformly dispersed loose porous structure. During the quick-freezing process, the removal of the ice crystal template forms a uniform porous structure on the surface of the magnetic beads, which makes FeCl3 highly dispersed, avoiding the problems of agglomeration and uneven coverage caused by traditional drying, and at the same time significantly improving Hg 0 Mass transfer and reaction efficiency.
[0016] (3) This invention expands the feasibility of low-cost iron-based mercury removal materials, breaks through the technical bottleneck of FeCl3 being difficult to load stably, and enables it to achieve high-efficiency mercury removal performance without relying on other metal additives, providing a new technical path for developing low-cost and environmentally friendly iron-based adsorbents.
[0017] (4) The present invention maintains excellent mercury removal performance under actual flue gas conditions. Due to the stable presence of the active components and the structure that is conducive to mass transfer, the modified magnetic mercury removal adsorbent exhibits excellent Hg removal performance in the temperature range of 100~160℃ for coal-fired flue gas. 0 It removes SO2 and enhances its resistance to interference from H2O.
[0018] This invention also provides a modified magnetic mercury removal adsorbent prepared by the method described above. This modified magnetic mercury removal adsorbent achieves stable loading and efficient utilization of Cl element, significantly improving the removal of Hg. 0 Adsorption performance. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation process of the modified magnetic mercury removal adsorbent in the examples; Figure 2 Hg of the adsorbents prepared in Example 2, Comparative Example 2, and Comparative Example 3 0 Removal efficiency comparison chart; Figure 3 Hg of the adsorbents prepared in Examples 1-3 and Comparative Example 1 0 Removal efficiency comparison chart; Figure 4 The modified magnetic mercury-removing adsorbent prepared in Example 2 removes Hg at different reaction temperatures. 0 Performance graph; Figure 5 The modified magnetic mercury removal adsorbent prepared in Example 2 removes Hg under different mixed flue gas compositions. 0 Performance graph; Figure 6 The Cl 2pXPS spectrum of the modified magnetic mercury removal adsorbent prepared in Example 1; Figure 7 The Cl 2pXPS spectrum of the modified magnetic mercury removal adsorbent prepared in Example 2; Figure 8 The image shows the Cl 2pXPS spectrum of the modified magnetic mercury removal adsorbent prepared in Example 3. Detailed Implementation
[0020] This invention provides a method for preparing a modified magnetic mercury removal adsorbent (FeCl3 / MF adsorbent), comprising the following steps: Modified magnetic beads were obtained by impregnating magnetic beads with FeCl3 solution; The modified magnetic beads are subjected to freeze treatment to obtain the modified magnetic mercury removal adsorbent. The freeze treatment includes sequential quick freezing and freeze drying, and the quick freezing temperature is -10°C. The concentration of the FeCl3 solution is 3~9wt%.
[0021] To address the key drawbacks of existing technologies, such as the easy hydrolysis of FeCl3 during conventional impregnation-heat drying, leading to the loss of Cl active components, uneven distribution of active sites, and structural densification that limits Hg0 diffusion and reaction efficiency, this invention provides a modified magnetic mercury removal adsorbent loaded with FeCl3 prepared through cryogenic treatment. Using magnetic beads as a carrier and FeCl3 as the active component, a non-liquid-phase drying environment of low-temperature freezing-vacuum sublimation (i.e., cryogenic treatment) is constructed to fundamentally inhibit the hydrolysis reaction of FeCl3, achieving stable loading and efficient utilization of Cl. Compared with existing CuCl2 modified systems, this invention avoids the problems of high cost and potential corrosion risks associated with copper-based materials. Furthermore, compared to the traditional FeCl3 impregnation-heat drying process, the introduction of cryogenic treatment effectively solves problems such as severe loss of active Cl, migration and aggregation of active components, and pore structure collapse, thereby significantly improving the adsorbent's ability to remove Hg0. 0 Its oxidation adsorption performance and structural stability.
[0022] Unless otherwise specified, all raw materials used in this invention are commercially available products in the field.
[0023] This invention utilizes FeCl3 solution to impregnate magnetic beads to obtain modified magnetic beads.
[0024] In this invention, the concentration of the FeCl3 solution can be 3wt%, 6wt%, or 9wt%.
[0025] The present invention preferably involves dissolving solid FeCl3 in water to obtain the FeCl3 solution for later use.
[0026] In this invention, the magnetic beads are preferably obtained from coal fly ash by magnetic separation, and the magnetic beads serve as a carrier. The material of the magnetic beads preferably includes Fe2O3 and Fe3O4.
[0027] In this invention, the water absorption rate of the magnetic beads is preferably 15-18%.
[0028] In this invention, the pore size of the magnetic bead is preferably 6.52~9.619 nm, and the specific surface area is preferably 0.380~0.6944 m². 2 / g.
[0029] In this invention, the impregnation is preferably an in-situ impregnation with equal volume, so that the volume of the FeCl3 solution matches the pore volume of the magnetic beads, ensuring that the FeCl3 solution does not completely submerge the magnetic beads.
[0030] In this invention, the preferred ratio of FeCl3 solution to magnetic beads is 0.15~0.18 mL:1 g, specifically 0.15 mL:1 g, 0.16 mL:1 g, 0.17 mL:1 g, or 0.18 mL:1 g.
[0031] In this invention, the impregnation process preferably includes sequential ultrasonic treatment and static setting.
[0032] In this invention, the preferred temperature for ultrasonic treatment is 5~10℃, and the preferred time is 20min. The purpose of ultrasonic treatment is to promote the uniform dispersion of FeCl3 solution on the surface of magnetic beads.
[0033] In this invention, the preferred temperature for settling is room temperature, and the preferred time is 2 to 6 hours, specifically 4 hours. The purpose of settling is to allow FeCl3 to be fully impregnated and loaded onto the surface of the magnetic beads.
[0034] After obtaining the modified magnetic beads, the present invention freezes the modified magnetic beads to obtain the modified magnetic mercury removal adsorbent. The freeze treatment includes quick freezing and freeze drying in sequence, and the quick freezing temperature is -10°C.
[0035] In this invention, the quick-freezing time is preferably 2 to 6 hours, specifically 4 hours; the quick-freezing causes the water inside the modified magnet to be rapidly converted into ice crystals, fixing the active ion sites.
[0036] In this invention, the quick-freezing is preferably carried out in an ultra-low temperature freezer.
[0037] In this invention, the freeze-drying temperature is preferably 0~10℃, the pressure is preferably 10Pa, and the time is preferably 36h; during the freeze-drying process, the water directly sublimates from the solid to the gaseous state and is removed to obtain the modified magnetic mercury removal adsorbent, namely FeCl3 modified magnetic beads.
[0038] In this invention, the freeze-drying is preferably carried out in a freeze dryer.
[0039] The present invention also provides a modified magnetic mercury removal adsorbent prepared by the preparation method described above, wherein the mass fraction of Cl element in the modified magnetic mercury removal adsorbent is 0.307~1.23%.
[0040] In this invention, (1) the hydrolysis reaction of FeCl3 solution needs to occur in a liquid water environment and at a certain activation energy, while the freezing treatment forcibly locks the reactants in a solid ice crystal matrix and operates at extremely low temperatures, thus completely suppressing the loss of active Cl from both thermodynamic and kinetic perspectives; (2) the voids left on the surface of the magnetic beads after the ice crystals sublimate retain their original occupied space, forming a loose modified layer similar to a "honeycomb", which greatly enhances the Hg 0 The efficiency of diffusion to the active site.
[0041] This invention also provides the application of the modified magnetic mercury removal adsorbent described in the above technical solution in the field of mercury removal from flue gas.
[0042] The present invention preferably uses the modified magnetic mercury-removing adsorbent to remove mercury from mercury-containing flue gas.
[0043] In this invention, the mercury-containing flue gas contains Hg 0 The preferred concentration is 50±3 μg / m 3 .
[0044] In this invention, the mercury-containing flue gas preferably also includes the following components at the following concentrations: O2: 0~10 vol%; SO2: 0~2000 ppm; NO: 0~1000 ppm; water vapor (H2O): 0~20 vol%; HCl: 0~20 ppm.
[0045] In this invention, the mercury removal temperature is preferably 100~160℃, specifically 100, 120, 140 or 160℃, and the time is preferably 30min.
[0046] In this invention, the flow rate of the mercury-containing flue gas is preferably 1.0 L / min.
[0047] In this invention, the modified magnetic mercury-removing adsorbent and Hg 0 The preferred mass ratio is 100:1.5.
[0048] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0049] Figure 1 The flowchart shown in the example illustrates the preparation process of the modified magnetic mercury removal adsorbent. Magnetic beads are impregnated with FeCl3 solution, followed by ultrasonic treatment and settling, and finally frozen to obtain the FeCl3 / MF adsorbent.
[0050] In this embodiment of the invention, the magnetic bead has a pore size of 6.52 nm and a specific surface area of 0.6944 m². 2 / g; The method for determining the mass fraction of Cl is X-ray photoelectron spectroscopy (XPS).
[0051] Example 1 The preparation of a modified magnetic mercury removal adsorbent includes the following steps: Magnetic separation: separating magnetic beads (composed of Fe2O3 and Fe3O4) from coal fly ash. Preparation of 3wt% impregnation solution: Add deionized water to a beaker, weigh out FeCl3 solid, dissolve it completely, and prepare a FeCl3 solution of the predetermined concentration for later use; Equal volume impregnation: Place the magnetic bead carrier in a beaker, and add FeCl3 solution to the magnetic beads according to the principle of equal volume impregnation, so that the solution volume matches the pore volume of the magnetic beads, ensuring that the solution does not completely submerge the magnetic bead carrier (1g of magnetic beads requires 0.15mL of solution). Ultrasonic treatment and settling: The resulting mixture was placed in an ultrasonic device for ultrasonic treatment for 20 minutes at a temperature of 5°C. After ultrasonic treatment, the mixture was settling at room temperature for 4 hours. Freezing treatment: The sample after standing was first quick-frozen (-10℃, 4h), and then transferred to a freeze dryer (-65℃) to freeze-dry the sample under low temperature (10℃) and vacuum conditions (10Pa) for 36h to obtain a modified magnetic mercury removal adsorbent, denoted as 3%FeCl3 / MF (or 3%FeCl3 / magnetic beads). The mass fraction of Cl element in the prepared modified magnetic mercury removal adsorbent was 0.307%.
[0052] Example 2 Same as Example 1, except that a 6wt% FeCl3 solution was prepared, denoted as 6%FeCl3 / MF or 6%FeCl3 / magnetic beads or freeze-drying method-6%FeCl3 / MF, and the mass fraction of Cl element in the modified magnetic mercury removal adsorbent was 0.614%.
[0053] Example 3 Similar to Example 1, the only difference is that a 9wt% FeCl3 solution was prepared, denoted as 9%FeCl3 / MF or 9%FeCl3 / magnetic beads, and the mass fraction of Cl element in the modified magnetic mercury removal adsorbent was 0.921%.
[0054] Comparative Example 1 Same as Example 1, except that a 0wt% FeCl3 solution was prepared, and the mass fraction of Cl in the resulting adsorbent was 0%.
[0055] Comparative Example 2: Preparation of Adsorbent by Thermal Drying Magnetic separation: separating magnetic beads (composed of Fe2O3 and Fe3O4) from coal fly ash. Preparation of 6wt% impregnation solution: Add deionized water to a beaker, weigh out FeCl3 solid, dissolve it completely, and prepare a FeCl3 solution of the predetermined concentration for later use; Equal volume impregnation: Place the magnetic bead carrier in a beaker, and add FeCl3 solution to the magnetic beads according to the principle of equal volume impregnation, so that the solution volume matches the pore volume of the magnetic beads, ensuring that the solution does not completely submerge the magnetic bead carrier (1g of magnetic beads requires 0.15mL of solution). Hot drying: The resulting mixture was dried at 120°C for 12 hours to obtain the adsorbent, denoted as hot drying method-6%FeCl3 / MF. The mass fraction of Cl in the prepared adsorbent was 0% (below the detection limit).
[0056] Comparative Example 3: Preparation of Adsorbent by Thermal Drying Magnetic separation: separating magnetic beads (composed of Fe2O3 and Fe3O4) from coal fly ash. Preparation of 6wt% impregnation solution: Add deionized water to a beaker, weigh out the CuCl2 solid, dissolve it completely, and prepare a CuCl2 solution of the predetermined concentration for later use; Equal volume impregnation: Place the magnetic bead carrier in a beaker, and add CuCl2 solution to the magnetic beads according to the principle of equal volume impregnation, so that the volume of the solution matches the pore volume of the magnetic beads, ensuring that the solution does not completely submerge the magnetic bead carrier. Hot drying: The resulting mixture was dried at 120°C for 12 hours to obtain the adsorbent, denoted as hot drying method-6%CuCl2 / MF. The mass fraction of Cl in the prepared adsorbent was 0.54%.
[0057] The specific surface area, pore volume, and pore size of the adsorbents prepared in Example 2 and Comparative Example 2 were tested, and the results are shown in Table 1. It can be seen that the specific surface area and pore size of the adsorbents prepared in this invention are only slightly improved and are not the main factors for mercury removal. The magnetic bead carrier is used to provide the FeCl3 loading matrix and magnetic separation performance, rather than as the main active adsorbent material.
[0058] Table 1. Test results of specific surface area, pore volume, and pore size of magnetic beads and adsorbents.
[0059] Adsorbent removal of Hg 0 experiment A fixed-bed test system was used to study the effect of adsorbent on Hg. 0 Adsorption and oxidation experiments.
[0060] The mercury removal performance of the adsorbent under different temperatures and gas conditions was tested. The experimental system simulated a total flue gas flow rate of 1.0 L / min and an initial Hg... 0 Concentration of 50 μg / m 3 Hg 0 Steam from standard Hg 0The permeation tube is placed in a U-shaped glass tube and heated in a constant-temperature water bath (temperature 55℃), then passed through N2 carrying Hg. 0 Other flue gas components (N2, O2, SO2, NO, H2O, and HCl) were supplied by compressed gas cylinders. Finally, the Hg at the reactor outlet was continuously recorded using an online mercury monitor. 0 concentration.
[0061] 100 mg of the adsorbents prepared in Example 2, Comparative Example 2, and Comparative Example 3 were weighed and placed into quartz tubes with an inner diameter of 7 mm. N2 and Hg were then introduced. 0 Steam mixing (total flow rate 1.0 L / min, Hg) 0 Concentration of 50 μg / m 3 Hg removal was carried out at a reaction temperature of 140℃ for 30 minutes. 0 Experiment. The mercury removal performance of the adsorbent was evaluated by measuring the breakthrough efficiency in the dynamic breakthrough curve. Figure 2 Hg of the adsorbents prepared in Example 2, Comparative Example 2, and Comparative Example 3 0 The comparison chart of removal efficiency shows that the modified magnetic mercury remover in Example 2 removes Hg more efficiently. 0 Performance (Hg) 0 The removal efficiency (93%) was superior to that of Comparative Example 2 (Hg). 0 The removal efficiency of 27% indicates that the 6% FeCl3 / MF prepared by the freeze-drying method inhibits FeCl3 hydrolysis, achieves high Cl element retention, and provides sufficient oxidation active sites. Compared with the hot-drying method of Comparative Example 3 - 6% CuCl2 / MF, the mercury removal performance is almost the same, indicating that the freeze-drying method has overcome the technical bottleneck of the difficulty in stabilizing FeCl3 loading, and adds a new technology for the development of low-cost, environmentally friendly iron-based adsorbents.
[0062] Weigh 100 mg of the adsorbent prepared in Examples 1-3 and Comparative Example 1 and place them into quartz tubes with an inner diameter of 7 mm. Then, introduce N2 and Hg into the tubes. 0 Steam mixing (total flow rate 1.0 L / min, Hg) 0 Concentration of 50 μg / m 3 Hg removal was carried out at a reaction temperature of 140℃ for 30 minutes. 0 Experiment. The mercury removal performance of the adsorbent was evaluated by measuring the breakthrough efficiency in the dynamic breakthrough curve. Figure 3 Hg of the adsorbents prepared in Examples 1-3 and Comparative Example 1 0 The removal efficiency comparison chart shows that 6% FeCl3 / MF removes Hg effectively. 0 Performance (Hg) 0 The optimal removal efficiency is 93%, with low FeCl3 loading (0 and 3%) for Hg. 0The limited number of active adsorption sites, coupled with a high FeCl3 loading (9%), hinders dispersion on the magnetic bead surface and impedes Hg adsorption. 0 Effective contact with active sites on 9% FeCl3 / MF.
[0063] The effect of different reaction temperatures on the removal of Hg by 6% FeCl3 / MF 0 Influence 100 mg of the adsorbent prepared in Example 2 was weighed and placed into quartz tubes with an inner diameter of 7 mm. N2 and Hg were then introduced. 0 Steam mixing (total flow rate 1.0 L / min, Hg) 0 Concentration of 50 μg / m 3 Hg removal was carried out for 30 minutes at different reaction temperatures (100℃, 120℃, 140℃, and 160℃). 0 Experiment. The mercury removal performance of the adsorbent was evaluated by measuring the breakthrough efficiency in the dynamic breakthrough curve. Figure 4 The adsorbent prepared in Example 2 removes Hg at different reaction temperatures. 0 The performance graph shows that, at reaction temperatures of 100~160℃, the overall removal of Hg is achieved. 0 The performance is good, Hg at 140℃ 0 The best removal performance (Hg) 0 Removal efficiency 93%), reaction temperature low or high, Hg 0 The removal performance was slightly reduced, indicating that at lower temperatures, it is difficult for all active sites to be activated, and at excessively high temperatures, the active components will be partially deactivated (decomposed and volatilized).
[0064] Different gas components affect the removal of Hg from 6% FeCl3 / MF 0 Influence 100 mg of the adsorbent prepared in Example 2 was weighed and placed into quartz tubes with an inner diameter of 7 mm. Different mixed flue gas components (N2, N2 + 4 vol% O2, N2 + 4 vol% O2 + 4 ppm HCl, N2 + 4 vol% O2 + 150 ppm NO, N2 + 4 vol% O2 + 600 ppm SO2, and N2 + 4 vol% O2 + 5 vol% H2O) and Hg were then introduced. 0 Steam mixing (total flow rate 1.0 L / min, Hg0 concentration 50 μg / m³) 3 Hg removal was carried out at a reaction temperature of 140℃ for 30 minutes. 0 Experiment. The mercury removal performance of the adsorbent was evaluated by measuring the breakthrough efficiency in the dynamic breakthrough curve. Figure 5 The adsorbent prepared in Example 2 removes Hg under different mixed flue gas components. 0 As shown in the performance graph, the adsorbent in Example 2 removes Hg under a 4 vol% O2 atmosphere. 0The performance impact is negligible. It has a promoting effect under an atmosphere of 4 ppm HCl or 150 ppm NO. It has a slight inhibiting effect under an atmosphere of 600 ppm SO2 or 5 vol% H2O. 0 The removal efficiency can still be maintained above 85%, indicating that the 6% FeCl3 / MF prepared by freeze treatment maintains excellent mercury removal performance under actual flue gas conditions and enhances the resistance to SO2 and H2O interference.
[0065] Figures 6-8 The images show the Cl 2pXPS spectra of the modified magnetic mercury removal adsorbents prepared in Examples 1-3, respectively.
[0066] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified magnetic mercury removal adsorbent, characterized in that, Includes the following steps: Modified magnetic beads were obtained by impregnating magnetic beads with FeCl3 solution; The modified magnetic beads are subjected to freeze treatment to obtain the modified magnetic mercury removal adsorbent. The freeze treatment includes sequential quick freezing and freeze drying, and the quick freezing temperature is -10°C. The concentration of the FeCl3 solution is 3-9 wt%; The impregnation is an in-situ impregnation with equal volume.
2. The preparation method according to claim 1, characterized in that, The quick-freezing time is 2-6 hours.
3. The preparation method according to claim 1, characterized in that, The ratio of FeCl3 solution to magnetic beads is 0.15~0.18 mL: 1 g.
4. The preparation method according to claim 1, characterized in that, The impregnation process also includes sequential ultrasonic treatment and settling.
5. The preparation method according to claim 4, characterized in that, The temperature for ultrasonic treatment is 5~10℃.
6. The preparation method according to claim 1, characterized in that, The freeze-drying temperature is 0~10℃, the pressure is 10Pa, and the time is 36h.
7. The modified magnetic mercury-removing adsorbent prepared by the preparation method according to any one of claims 1 to 6, characterized in that, The mass fraction of Cl in the modified magnetic mercury removal adsorbent is 0.307~1.23%.
8. The application of the modified magnetic mercury removal adsorbent according to claim 7 in the field of mercury removal from flue gas.